INTEGRAL AND QUALIFIED CRIMINAL LAW ENFORCEMENT MODEL IN DEALING WITH VEHICLE ROBBERY: A LEGAL STRENGHTENING - Heni Siswanto; Maroni Maroni; Fathoni Fathoni (Universitas Muhammadiyah Metro, 2017)
The crime of theft with violence, theft of motorcycles, and robbery have spread terror massively. It becomes a very frighteningly specter for people in Lampung. To resolve it, it is necessary to build a